2017
DOI: 10.1142/s2010135x1720003x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of composite based on ferroelectric copolymer of poly(vinylidene fluoride-trifluoroethylene) and ferroelectric ceramics of barium lead zirconate titanate

Abstract: A study of dielectric properties of composite films on the base of poly(vinylidene fluoride-trifluoroethylene) copolymer P(VDFTrFE) and ferroelectric ceramics of barium lead zirconate titanate (BPZT) solid solution is presented in this work. The composite films containing up to 50 vol.% of BPZT grains with size $1 m were prepared by the solvent cast method. Frequency dependences of real and imaginary components of the complex permittivity were determined. The concentration dependence of the dielectric constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…PVDF-Trfe/CNTs/BTO piezoelectric films with arranged micropores were prepared by the casting method (see Figure 1b). [31,32] The piezoelectric film functioned as both a separator and an energy harvester. [33] Figure 1c shows the entire structure of the SCSPC device assembled from ZnO@Mo-Fe-MnO 2 NA electrodes and PVDF-Trfe/CNTs/BTO piezoelectric thin films.…”
Section: Resultsmentioning
confidence: 99%
“…PVDF-Trfe/CNTs/BTO piezoelectric films with arranged micropores were prepared by the casting method (see Figure 1b). [31,32] The piezoelectric film functioned as both a separator and an energy harvester. [33] Figure 1c shows the entire structure of the SCSPC device assembled from ZnO@Mo-Fe-MnO 2 NA electrodes and PVDF-Trfe/CNTs/BTO piezoelectric thin films.…”
Section: Resultsmentioning
confidence: 99%
“…Such composites combine the flexibility, light weight, and high dielectric strength of polymers with the large dielectric permittivity, and piezoelectric and pyroelectric coefficients of inorganic ferroelectrics. It is shown that the introduction of ferroelectric nanoparticles, such as BaTiO 3 , Pb(Zr,Ti)O 3 , or TGS, into polymers yields capacitors with significantly enhanced piezoelectric and pyroelectric coefficients, as well as stored energy density [20][21][22][23][24][25][26][27][28][29][30][31][32]. The morphology of the filler, its volume fraction, the surface properties of the filler, the properties of the polymer-filler interface, and the distribution of the filler in the polymer matrix play important roles in optimizing the energy storage properties.…”
Section: Introductionmentioning
confidence: 99%